The Nature of Preprinciple in Energetic Metaphysics - Mordarski, Ryszard (Sensus Historiae, 2022)
In this article I focus on two issues: the reconstruction of intellectual traditions that lie at the base of energetic metaphysics, and the discussion of basic attributes assigned to God-Preprinciple in energetic metaphysics: aseity, immutability, eternity and personality.